THE EFFECT OF REWARD AND PUNISHMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE THROUGH WORK DISCIPLINE - Harini Pujianti; Agustin HP; Hary Sulaksono (MBA - Journal of Management and Business Aplication, 2022)
The purpose of this study was to determine the direct or indirect effect of Reward andPunishment and work motivation on employee performance through work discipline as anintervening variable on employees of the Public Works and Spatial Planning Office ofBondowoso Regency. The total population of this study was 266 with a sample of 40respondents. The sampling technique used was purposive sampling. The analytical techniqueused is path analysis using SPSS 22.0. The results of data analysis show that the Reward andPunishment variable has a significant effect on work discipline, work motivation has asignificant effect on work discipline, Reward and Punishment has a significant effect onemployee performance, work motivation has a significant effect on employee performance ,work discipline has a significant effect on employee performance.Keywords: Reward And Punishment, Work Motivation, Work Motivation and EmployeePerformance